Seasonality in Equity Market : New Evidence from Four Emerging Market - Ruzita Abd Rahim; D. Agus Harjito (Universitas Islam Indonesia, 2006)
This study investigates the existence of seasonality effect in Malaysia and its three neighboring markets− Indonesia, Singapore, and Thailand– using a sample of 24 selected sectoral and broad indexes over the period of January 1988 to December 2005. This study also examines the influence of trading activity on the market anomaly by dividing the 18-year sample period into thin and active trading sub-periods. The existence of seasonality effect is revealed using a non-parametric Mann-Whitney U test, which later is verified using time-series regression. Considerable evidence in favor of February effect is obtained in Malaysia from the Mann-Whitney U tests in the full period and particularly in the active trading sub-period but it nearly disappears in the thin trading sub-period. While slight evidence of December effect is detected in Singapore and Indonesia, January effect is nearly non-existence in Thailand. In the meantime, the influence of trading activity on seasonality effect is only confined to the equity market of Malaysia. The results from time-series regressions are consistent with these findings. Given the fact that none of these emerging markets impose tax on capital gains, the existence of seasonality effect in month other than the tax-month provides additional evidence against the tax-loss selling hypothesis. Overall, the study concludes that while all except Thailand suggest the presence seasonality effect, from an investment perspective, only in the case of Malaysia the effect seems strong enough to command an exploitable strategy but even then, such rule should be of comfort only if applied in the active-trading period. Keyword: Seasonality Effect; February Effect; Trading Activity; Emerging Markets